Experience in Oceanographic Surveys for Designing 100 kW Tidal Current Energy Conversion Systems - Mukhtasor, Mukhtasor; Rasgianti, Rasgianti; Junianto, S; Lestari, S; Rahmawati, S; Erwandi, Erwandi; Ikhwani, H; Pratikto, W A; Nugraha, A D; Simaremare, A A; Ruly, Ruly (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
Nowadays tidal current energy conversion system (TCECS) is being developed with a capacity of 100 kW for Indonesian waters. The design process is based on the results of field measurements, i.e., ocean currents, tides, ocean waves, and bathymetry. This paper aims to explain the experiences when collecting oceanography data in a potential site for TCECS. The survey method is that the equipment placed on the seabed will emit signals that can record flow and wave data according to the desired time and depth. The survey process, especially for the tidal current energy application, requires good preparation so as not to fail. The results of this paper explain the challenges and highlight the steps. These are technical, environmental, and survey permits. The technical aspects are tool stability, buoyancy effects, visualization tools with an underwater camera system, seawater brightness, and sedimentation. Environmental aspects are big waves, strong currents, and weather. The survey permit aspects are destruction and conservation area. Therefore, before the survey, safety procedures or documents must be made in the form of HIRA (Hazard Identification and Risk Analysis). The experiences of this survey are a novelty consideration for other surveyors in the tidal current energy aspect.